KAJIAN KONSEPTUAL TENTANG PENINGKATAN KINERJA MELALUI PEMOTIVASIAN DAN PEMBERIAN KOMPENSASI - Reresi, Marsianus (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2016)
This article intends to provide some important features in relation to performance improvement through motivating and awarding compensation. The central question which I endeavour to answer in this piece of writing is “How to improve the performance of members of the organization?” Motivating and awarding compensation become managerial strategy solutions in an effort to improve the performance of the organization’s members.